Adverse events associated with mTOR inhibitors. (March 2013) - Pallet, Nicolas; Legendre, Christophe
<x xml:space="preserve">Abstract</x> Introduction: The mTOR (mechanistic target of rapamycin, formerly known as mammalian target of rapamycin) kinase is centrally involved in the regulation of cell growth and metabolism in response to intra- and extracellular energetic stimuli and growth factors. The importance of mTOR in health and diseases has fueled the development of molecules that inhibit mTOR signaling, including rapalogs (sirolimus, temsirolimus, everolimus and deforolimus), which complex with FK506-binding protein 12 (FK-BP12) to inhibit mTOR complex 1 (MTORC1) activity in an allosteric manner, or the more recent ATP-competitive mTOR inhibitors (mTORi), which target the catalytic site of the enzyme. However, clinical development of these mTORi has revealed that these drugs produced numerous side effects that could be serious and/or debilitating. Despite pharmacological efforts to develop drugs with an improved safety profile, these side effects are often unpredictable and may frequently preclude the efficiency of mTORi. Areas covered: The objective of this review is to perform a comprehensive survey of the safety profiles of various rapalog-based therapies from the available clinical literature. The authors will discuss the potential mechanisms of these therapies, taking into account the knowledge of the biological pathways regulated by mTOR. Expert opinion: A better prevention and management of mTORi-related side effects requires the identification of alterations in related biological pathways that will help to delineate therapeutic targets.